Analisis Emisi Gas Rumah Kaca Pada Pengelolaan Sampah di Institut Teknologi Kalimantan Menggunakan Metodologi Intergovernmental Panel on Climate Change: Analisis Emisi Gas Rumah Kaca Pada Pengelolaan Sampah di Institut Teknologi Kalimantan - Bunga', Samuel; Rahendaputri, Chandra Suryani; Yorika, Rahmi; Rini, Intan Dwi Wahyu Setyo; Maulana, Melisa Triandini (LPPM ITK, 2025)
Institut Teknologi Kalimantan uses a solid waste disposal system for waste management. Waste is being delivered straight to the dump (TPA) without any kind of processing or recycling. The goal of this research is to analyze greenhouse gas emissions generated from the current waste management practices at Institut Teknologi Kalimantan, as well as to evaluate emissions under Three alternative scenarios. The research method complies with IPCC 2019. Scenario 1 integrated landfilling with organic waste composting and a high recycling rate (RF: 80%). Scenario 2 involved waste incineration, organic waste composting, and a moderate recycling rate (RF: 50%). Finally, Scenario 3 focused on waste incineration combined with organic waste composting. The research findings indicate that paper waste is the largest contributor to greenhouse gas emissions in Scenario 0, accounting for 52% of the total emissions produced. Among the three scenarios analyzed, Scenario 3 generated the highest overall greenhouse gas emissions. In this scenario, waste incineration emerged as the predominant source, contributing 93% of the total emissions in Scenario 3. The types of waste contributing to greenhouse gas emissions in solid waste disposal under Scenario 0 are organic waste (food scraps), paper waste, and wood waste. Among these, paper waste produces the highest greenhouse gas emissions due to its high Degradable Organic Carbon (DOC) content. Based on the three scenarios, and assuming without considering economic aspects or control measures, waste incineration was found to produce the highest emissions compared to landfill disposal and composting.